A Comparative Study on Register and Genre of Review Texts in Teen Ink Magazine - Qudwatu Nabila Rodhiya (Jurnal Bahasa, Sastra, dan Studi Amerika, 2019)
This research focuses on two review texts published in a teenage magazine called Teen Ink. It is aimed to discover the language style and text structure used by the same text producer. Using Systemic Functional Linguistics (SFL) approach, this research describes the register and genre employed in the two analyzed texts. The analysis was done by examining and comparing the generic structure and the metafunctions of each text. The description of data led to the interpretation of field, tenor, and mode. From the genre analysis, it can be seen that the text producer follows the same text structure for both texts, though differences were found in the technique used to compose each stage of the text. In terms of register, different dominant transitivity and circumstance types were found in both texts. Meanwhile, the text producer puts all participants surrounding the texts in equal position, and positive assessment is implied in both texts. In addition, as the texts are written in a language style that tends to be spoken, the texts are considered appropriate for the medium, namely the review column of Teen Ink magazine.